Challenges of Court Orders Enforcement - MATEIKOVICH, Maksim (Journal of Advanced Research in Law and Economics; Vol 8 No 3 (2017): JARLE Volume VIII Issue 3(25) Summer 2017, 2017)
Enforcement of court orders remains an acute problem even in developed countries. The study aims to analyze how well court orders are enforced in different countries, including the United States, the European Union, and the Commonwealth of Independent States, to identify its strong and weak sides. Comparative jurisprudence was chosen as the leading research method, and it allowed analyzing the features of various systems of judgments execution. The empirical material was formed by some decisions of the European Court of Human Rights and the reports of the European Commission on the Efficiency of Justice. The article substantiates the possibility of effective coexistence of the state and private systems for the enforcement of court orders. The author names the judge making the wrong choice of the means of restoring the violated law and order as one of the reasons leading to non-enforcement of court orders. The article discusses the minimum qualification level of the bailiff and vocational guidance for students pursuing a degree in law for future work in this field. The central idea of the paper is that implementation of judicial decisions is an element of the efficient justice, without which the rule of law is impossible.